LA COMPETITIVIDAD Y LOS CLUSTERS COMO ELEMENTO DE DESARROLLO DEL PAÍS - Begazo Villanueva, José Domingo (2004)
Competitiveness becomes either the country or the company capacity to generate more wealth that of their competitors in the market world. On the other hand, a cluster becomes the geographical concentration of companies groups being nourished mutually by means of vertical relationships (cuslomers, technology and distribution channels) developing tecnological adoances and thus being integrated by customers. Thus it can be inferred from both concepts that the cluster conformation generates the competitiveness whic is the main Jeature in the country development.